Efficacy of Topical Sinecatechins Ointment for Provoked Vestibulodynia in Post-Menopausal Women: A Randomized Double-blind Placebo-Controlled Clinical Trial. (1st August 2022) - Nachtigall, L; Krause, C; Harris, D; Greene, M; Enzenbacher, J
ABSTRACT: Introduction: Introduction: There is an unfulfilled need in post-menopausal women for a non-hormonal therapeutic to alleviate provoked vestibulodynia. Most post-menopausal women choose not to use estrogens and for others with estrogen sensitive malignancies estrogens are contraindicated. Vestibulodynia may persist despite the use of estrogens for post-menopausal women with vulvovaginal atrophy. Others experience vestibulodynia in the absence of vulvovaginal atrophy. Objective: Objective: To determine efficacy of low dose, topical sinecatechins ointment, an FDA approved, antiproliferative, botanical drug derived from green tea, in reducing provoked vestibulodynia in sexually active postmenopausal women. Methods: Methods: 32 postmenopausal sexually active women with a chief complaint of secondary provoked vestibulodynia were studied. Vestibulodynia was evaluated by standardized Q-TIP Testing and subjective reporting with a pain intensity at least a 7 on a 0-10 point Numerical Rating Scale (NRS) where (0) no pain; (1-3) mild pain; (4-6) moderate pain;(7-9) significant pain; (10) severe pain. Subjects were evaluated by the gynecologist every 2-3 weeks for a total of 3 office visits during which vaginal pH and vaginal maturation index were performed. Subjects applied ½ inch of ointment once daily (5% sinecatechins, 10% sinecatechins or placebo) to their vulvar vestibule, avoiding the urethral introitus. Subjects were instructed to immediately report any irritation and to reduce their use to three times per week. Results: There was no significant difference in the average vestibular pain between groups, (placebo, 5%, 10% sinecatechins ointment) at baseline. Both 5% and 10% active drug groups showed a progressive decrease in the one-way ANOVA P-Values with each visit, indicating a greater degree of pain reduction with continued use of the active study drug. Based on the Q-TIP and NRS, the 5% sinecatechins group demonstrated early pain reduction at Visit 2, while the 10% sinecatechins group demonstrated pain reduction by final Visit 3, most likely attributed to irritation experienced by several subjects using 10% which resolved by the final visit with decreased frequency of use to no more than 3x/week. All study groups showed no significant change in vaginal maturation index or vaginal pH between initial and final visits. Although not the primary objective of this clinical trial, several subjects indicated that topical 10% sinecatechins ointment used 3x/week increased sexual arousal, increased lubrication and/or decreased latency to orgasm without causing irritation. Conclusions: Topicals sinecatechins ointment, significantly reduced provoked vestibulodynia in postmenopausal women offering a novel therapeutic alternative for the alleviation of vestibulodynia for women with a history of an estrogen sensitive malignancy, including those on an aromatase inhibitor. Sinecatechins ointment may be used adjunctively for women successfully using estrogens to treat vaginal atrophy to alleviate persistent vestibulodynia and enhance sexual experience. The observed clinical effects of topical sinecatechins ointment on reducing vestibulodynia was dependent on both the concentration of sinecatechins and the frequency of application. Additional clinical trials for pre- and post-menopausal women with topical sinecatechins ointment as an adjunctive or primary therapeutic for sexual pain and arousal and orgasm are needed. Disclosure: Yes, this is sponsored by industry/sponsor: GTO Pharmaceutical, LLC Clarification: Industry funding only - investigator initiated and executed study